Implementasi Sistem Manajemen Mutu Pelayanan Keperawatan Melalui Kepemimpinan Mutu Kepala Ruangan - Aziz Alimul Hidayat; Ana Pratiwi; Ratna Agustin (Jurnal Ners, 2016)
Introduction: The quality management system is an order that ensures the achievement of goals and quality objectives which are planned in nursing care. One of the factors that may affect the implementation of quality management systems in the inpatient units is the quality leadership of head nurse. This study aims to determine the effect of the quality leadership of the head nurse to the implementation of quality management systems of nursing cares in hospital.Methods: The research method uses analytical research with cross-sectional approach. The sample of this study consists of eight wards; They are Multazam pavillion, Arofah, Sakinah, Shofa Marwah, Annisa, Mina, Ismail, and ICU which meet with the inclusion and exclusion criteria. The data was taken by using simple random sampling. The data collection by using questionnaires, interviews and observation. Data analysis used a simple statistical linear regression tests with a significance the value of α ≤ 0.05.Results: The results showed that the quality of leadership of the head of wards is mostly good (50%) and the implementation of quality management system of nursing care is mostly good (62.5%). Results of analysis of the simple linear regression test on the influence of leadership quality of the head nurse through the implementation of the quality management system of inpatient units (ρ = 0.024).Conclusion: The results of this study expect the nurses to increase the commitment and responsibility in implementing the quality management system of nursing cares in the inpatient units so as to achieve the excellent quality of nursing cares and can boost confidence, satisfaction of patients, families, and communities on nursing care.